New media and old stereotypes. Images and discourses about drunk women and men on YouTube. Issue 5 (2nd September 2016) - Rolando, S.; Taddeo, G.; Beccaria, F.
Abstract : Female alcohol consumption has long been judged more harshly than male behaviour of the same nature. Scholars have shown that traditional mass media contribute to strengthening these stereotypes. The hypothesis of the present study is that new media, especially Web 2.0 environments, provide room for rewriting gender roles in relation to alcohol. To test this hypothesis, 2000 videos were retrieved on YouTube using a list of Italian keywords relating to drunkenness. The 142 most frequently viewed clips were then analysed through a multilayer visual ethnography method. It was found that representations of drinking practices on YouTube seem to reflect the conventional double standard. Female drinking is mainly interpreted as a sign of sexual willingness, and is strongly stigmatised. In most cases, moreover, women themselves actively contributed to creating the sexual meaning, both as video protagonists and as commenters. Analysed materials seem to show that even in a user-generated content medium such as YouTube, old gender stereotypes about drinking fail to be deconstructed. Conversely, the images and discourses that were analysed reinforce these stereotypes, reproducing the messages conveyed by mainstream media in an even more explicit and risky manner.